Uporaba ocenjevalnih lestvic pri ocenjevanju samostojnosti pacienta v rehabilitacijski zdravstveni negi - Petkovšek Gregorin, Romana (Obzornik zdravstvene nege, 2017)
Introduction: Functional assessment of patient's independence is a systematic attempt to evaluate their abilities. The aim of the literature review was to determine which assessment scales are most frequently used in rehabilitation nursing and to assess their usefulness. Methods: A systematic review of the literature was conducted. The research was done in December 2015 using the following databases: CINAHL, PubMed, COBIB.SI and the article database of the Slovenian Nursing Review journal. The following keywords in English were used: rehabilitation scales, rehabilitation, dependency, assessment outcome. The Boolean AND operator was used. From the total of 416 results, 19 articles were included in the final analysis. Results: Five content categories were developed: (1) the most frequently used assessment scales for assessing patient's independence and progress in nursing, (2) the validity and reliability of assessment scales, (3) a comparison of assessment scales, (4) the use of assessment scales, and (5) the impact of nurses on increasing patients' independence. Discussion and conclusion: There are numerous assessment scales that describe patient's functional independence. The Barthel Index scale is most often used, followed by a combined Functional Independent Measure + Functional Assessment Measure and Northwich Park Dependency Scale, which are among the most reliable for the use in rehabilitation health care. The latter two provide for a full assessment of a patient's nursing needs, and monitoring and evaluating work.
Keywords: assessment of the functional status; izid rehabilitacije; ocena funkcionalnega stanja; outcome of rehabilitation; pacienti; patients; rehabilitacija; rehabilitation; vocational rehabilitation